Formulation of Popped Pearl Millet (Pennisetum glaucum) Bar and their Nutritional and Sensory Attributes - Ritu, Karuna Singh, Anjani Kumar and Rashmi Singh, (Indian Journal of Extension Education, 2023)
The present study aimed at making the millets available to people in ready-to-eat form with some enhancednutritional properties. A bar was developed through popping processing using pearl millet as main ingredient.The breakfast cereal was prepared by heating, mixing and cooling popped pearl millet, popped amaranth,puffed Bengal gram, flax seeds, sunflower seeds, raisins, and sugar. The product was found to have 10.84per cent protein, 4.39 per cent fat, 5.43 per cent fibre, 3.17 mg/100g zinc, 5.13 mg/100g iron and 215.63mg /100g phosphorus. The popped pearl millet bar developed in the present study was nutritionally superiorand can be used as a novel product. Therefore, it could be concluded that pearl millet grain has a wide rangeof opportunity for utilization in production of ready-to-eat, nutritionally rich cereal bar products along withbetter sensory qualities, which on commercial scale may open new avenues for better marketing andutilization of this important but underutilized grain.